2021
DOI: 10.1021/acsami.1c10359
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Enabled Models to Predict Sulfur Solubility in Nuclear Waste Glasses

Abstract: The U.S. Department of Energy is considering implementing the direct feed approach for the vitrification of low-activity waste (LAW) and high-level waste (HLW) at the Hanford site in Washington state. If implemented, the nuclear waste with a higher concentration of alkali/alkaline-earth sulfates (than expected under the previously proposed vitrification scheme) will be sent to the vitrification facility. It will be difficult for the existing empirical models to predict sulfate solubility in these glasses or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…As can be seen, this model unites the fast Fourier transformation (FFT) algorithm with the deep learning (DL) model. Details of the DL model-which is premised on the random forests model that has been in our previous studies (Cook et al, 2021b;Lapeyre et al, 2021;Xu et al, 2021)-can be found in Supplementary Section S1 of Supplementary Information S1…”
Section: Modeling Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen, this model unites the fast Fourier transformation (FFT) algorithm with the deep learning (DL) model. Details of the DL model-which is premised on the random forests model that has been in our previous studies (Cook et al, 2021b;Lapeyre et al, 2021;Xu et al, 2021)-can be found in Supplementary Section S1 of Supplementary Information S1…”
Section: Modeling Methodsmentioning
confidence: 99%
“…The FT-DL model described in section 2.0 differs from the ML models used in our previous studies (Cook et al, 2021b;Lapeyre et al, 2021;Xu et al, 2021) (i.e., DL model based on random forests) in one key respect: In the FT-DL model, the database is FFT-transformed, prior to the model's training, so as to reduce the database's dimensionality; whereas in the DL model, the database is used in its pristine form. In section 2.0, it was argued that the FFT-transformation of the database ensures better training of FT-DL model; thereby, resulting in improvement of its prediction performance.…”
Section: Validation Of the Ft-dl Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, crucible-scale sulfur solubility tests have been used to augment melter test results to develop a compositional model. 14,[26][27][28][29][30][31] The model approach includes predicting sulfur solubility by the compositional model and then calculating melter tolerance values based on the correlation between the sulfur solubility and the melter tolerance. However, it is not clear how the two values are correlated.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the cost and time required to perform melter tests, the directly measured melter tolerance data are limited. Instead, crucible‐scale sulfur solubility tests have been used to augment melter test results to develop a compositional model 14,26–31 . The model approach includes predicting sulfur solubility by the compositional model and then calculating melter tolerance values based on the correlation between the sulfur solubility and the melter tolerance.…”
Section: Introductionmentioning
confidence: 99%